Peningkatan Literasi Green Economy Berbasis Syariah Melalui Pembuatan Produk Alami dan Pelatihan Digital Marketing - Anantyasari, Malta; Sarwono, Sarwono; Alvyana, Alvyana (Journal of Community Development, 2024)
The literacy of green economy among Indonesian people is still very minimal so that its implementation is still very low. The concept of green economy is closely related to social welfare, environmental sustainability, and renewable energy, biodiversity, and emission reduction. Green economy answers the economic challenges in Indonesia, which lately is still rampant exploitation in the field of natural resources. In addition, the concept of green economy is very relevant to the concept of sharia economics or Islamic economics which both carry out the principle of environmental sustainability and prohibit things that cause damage. However, the two economic concepts are still not well implemented due to the lack of literacy among the community. To answer these problems, researchers decided to increase literacy in the field of green economy and Islamic economics which was carried out through socialization and making environmentally friendly products and coupled with digital marketing training, because digital marketing is in line with the principles of green economy where practically, digital marketing is a very environmentally friendly sales and promotion method because it does not use media derived from the exploitation of natural resources. This community service activity was carried out at the Darul Ulum Islamic boarding school, Kasihan village, Tegalombo sub-district, Pacitan district. The socialization participants were students from the boarding school.